Physical modeling of buried PVC pipes overlying localized ground subsidence - Costa, Yuri Daniel Jatobá (2020)
The last half-century has witnessed a proliferation in the use of polyvinyl chloride (PVC) pipes in civil engineering applications. However, little physical data are available to date to assess conformance with performance limits of these pipes subjected to events involving localized ground subsidence. In this study, experimental results are generated and evaluated from a series of physical models involving a buried PVC pipe overlying a localized subsiding bedding zone. Ground subsidence was simulated using a precisely controlled trapdoor system positioned at mid-length of the pipe. A technique including the use of a custommade displacement transducer was developed as part of this study to facilitate collection of continuous deflection profiles along the axis of the pipes. The progressive development of soil arching was also monitored using earth pressure sensors placed on the top, sides, and at several locations beneath the pipe, both within and beyond the zone of ground subsidence. Strains in the external wall of the pipe were also monitored. The results indicate that significant bending developed in the portion of the pipe traversing the subsidence zone, especially at the pipe crown. Beyond this point, radial deflections of the pipe cross section continued to be detected along the pipe length to distances of approximately four pipe diameters. Ground subsidence induced a severe redistribution of the earth pressures measured in the soil mass surrounding the pipe. A significant increase in vertical soil pressures beneath the pipe was captured within a distance of about one pipe diameter outside the subsidence zone. The overall response of the PVC pipe to localized ground subsidence was found to improve with increasing backfill density and decreasing soil confinement